2021
DOI: 10.21203/rs.3.rs-863159/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strengthening the Service Experiences of Women Impacted by Gambling-related Intimate Partner Violence.

Abstract: BackgroundWhile problem gambling does not directly cause intimate partner violence (IPV), it exacerbates that violence significantly. Women experiencing both gambling harm and IPV often find themselves in challenging situations; furthermore, stigma and shame frequently act as barriers to seeking help from health and social service agencies. Despite the links between problem gambling and IPV, little is known about women’s experiences of using support services for both IPV and gambling related issues. This paper… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The widespread availability and promotion of gambling [50][51], and the failure to reduce gambling problems in Australia [52], continue to exacerbate the impacts of IPV for women and their children. Practical support aimed at encouraging women to manage their nances and build self-e cacy can provide a useful mechanism to reduce further gambling-related harm [53][54]. More broadly, policy, regulatory and gambling industry changes are needed to reduce gambling problems and their effects on IPV.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread availability and promotion of gambling [50][51], and the failure to reduce gambling problems in Australia [52], continue to exacerbate the impacts of IPV for women and their children. Practical support aimed at encouraging women to manage their nances and build self-e cacy can provide a useful mechanism to reduce further gambling-related harm [53][54]. More broadly, policy, regulatory and gambling industry changes are needed to reduce gambling problems and their effects on IPV.…”
Section: Discussionmentioning
confidence: 99%
“…In Suomi et al's (2013) study, the 11 interviewees who had perpetrated violence against a family member reported that their violence was fueled by their accumulated anger and mistrust arising from the victim's gambling. However, perpetrators' explanations for their violence are unreliable, since they frequently use victim-blaming and external "causes" to justify their violence (Henning and Holdford, 2006), including blaming the victim's gambling (Browne et al, 2016;Hing et al, 2020;O'Mullan et al, 2022a). Nevertheless, problem gambling undoubtedly has deleterious effects on families.…”
Section: Explanations For Links Between Gambling and Dfv/ipv Victimiz...mentioning
confidence: 99%
“…Where gambling precedes the violence, these accumulated tensions and emotions may trigger situational violence in direct response to the victim's gambling (Korman et al, 2008;Suomi et al, 2013Suomi et al, , 2019. However, the ANROWS study (Hing et al, 2020(Hing et al, , 2022dO'Mullan et al, 2022a) found that only a minority of the women interviewed first experienced IPV after they started gambling. Further, their subsequent victimization was not always limited to violent incidents that were an immediate response to their gambling, although these continued to occur.…”
Section: Explanations For Links Between Gambling and Dfv/ipv Victimiz...mentioning
confidence: 99%
See 2 more Smart Citations